Respuesta :

[tex]9 \times ( {3}^{n - 2} ) = {27}^{n + 1} \\ [/tex]

[tex] {3}^{2} \times {3}^{n - 2} = ({ {3}^{3} })^{n + 1} [/tex]

====================================================

Hint :

[tex] {a}^{b} \times {a}^{c} = {a}^{b + c} [/tex]

&

[tex] ({ {a}^{b} })^{c} = {a}^{b \times c} [/tex]

====================================================

[tex] {3}^{n - 2 + 2} = {3}^{3 \times (n + 1)} [/tex]

[tex] {3}^{n} = {3}^{3n + 3} [/tex]

====================================================

Hint :

[tex] {a}^{b} = {a}^{c} [/tex]

[tex]b = c[/tex]

====================================================

[tex]n = 3n + 3[/tex]

Switch sides

[tex]3n + 3 = n[/tex]

Subtract both sides minus 3

[tex]3n + 3 - 3 = n - 3[/tex]

[tex]3n = n - 3[/tex]

Subtract both sides minus n

[tex]3n - n = n - n - 3[/tex]

[tex]2n = - 3[/tex]

Divide both sides by 2

[tex] \frac{2n}{2} = \frac{ - 3}{2} \\ [/tex]

[tex]n = - \frac{3}{2} \\ [/tex]

ACCESS MORE